Children's Diets, Nutrition Knowledge, and Access to Markets. (July 2017) - Hirvonen, Kalle; Hoddinott, John; Minten, Bart; Stifel, David
Highlights: Undernutrition in Ethiopia is widespread and children consume monotonous diets. We study the impact of better nutrition knowledge on improving dietary diversity. We also assess how this relationship varies by market access. Better nutrition knowledge leads to large improvements in dietary diversity. But only in areas with relatively good market access. Summary: Chronic undernutrition in Ethiopia is widespread and many children consume highly monotonous diets. To improve feeding practices in Ethiopia, a strong focus in nutrition programing has been placed on improving the nutrition knowledge of caregivers. In this paper, we study the impact of caregivers' nutrition knowledge and its complementarity with market access. To test whether the effect of nutrition knowledge on children's dietary diversity depends on market access, we use survey data from an area with a large variation in transportation costs over a relatively short distance. This allows us to carefully assess the impact of nutrition knowledge with varying access to markets, but still within similar agro-climatic conditions. Using an Instrumental Variable approach, we find that better nutrition knowledge leads to considerable improvements in children's dietary diversity, but only in areas with relatively good market access. Our findings suggest that policymakers and program implementers need to ensure that efforts to improve nutrition knowledge are complemented by efforts to improve access to food.